What Professional Service Firms must do to Thrive. - Nanda Ashish; Narayandas Das (Mumbai Apex Pvt. Ltd., 2021)
They have to tightly align their practices and clients. A diffuse profile dilutes a practices identity and renders it a jack of all trades and a master of none.
Keywords: General Management